(untitled) (Revista Internacional de Formação de Professores, 2018)
This text is part of the study of the initial training of teachers of the field education. It aims to historian the process of development of the course of pedagogy, of the project of initial formation teaching of pedagogy of the Earth, of the University of the state of Rio Grande do Norte, with emphasis for its constitution in the institution. It is a qualitative study that is based on the oral history research method. From thematic interviews with the coordinator of the course and with a former, participant of the training in the said degree, we consider that the process constituting this first initial training initiative in the framework of the University of the State Of the Rio Grande do Norte was marked by both institutional challenges and barriers, as a personal imprint by the graduates, being overcome by the collective actions of the subjects involved with the formative proposal considered for the course.